E-Training Modeling Sistem Pada Balai Latihan Kerja Menggunakan Metode Zachman Framework - Lesmana, Seko; Muslih, Muhamad; Saepudin, Sudin (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
UPTD Sukabumi District Vocational Training Center is a government agency that functions as a training ground for people who want to deepen their expertise in their respective fields. Currently, information services about the training of the UPTD at the Sukabumi District Vocational Training Center have not been presented optimally. Training information in the form of vocational training, training instructors and other data still uses social media such as Facebook to inform services to the public. This becomes a problem because it is less efficient in conveying information and is not comprehensive. This study aims to optimize information services about the training of the UPTD Work Training Center in Sukabumi Regency. To achieve this optimization, a job training information system is needed to make it easier to present training information. This research focuses on training information services that provide convenience in providing information about the vocational openings, training schedule, participant quota and other information related to the UPTD training at the Sukabumi District Vocational Training Center. The approach in this study uses the Zachman Framework approach which was developed using the PHP 7 programming language and MySQL database. The result of this research is a website-based job training information system design.